Human Capital Development as a Mechanism for Improving Patient Healthcare During the COVID-19 Crisis - akchouche, soumia; Fortas , Fatiha (Journal of Excellence for Economics and Management Research, 2025)
This study aims to provide an analytical perspective on human capital development as a mechanism for improving patient healthcare during the COVID-19 crisis, highlighting key methods and approaches for effective investment in human capital. Its significance lies in identifying the strategies that significantly impact patient healthcare during crises to leverage them for future crisis management. A questionnaire was distributed to a sample of 55 employees from the Anesthesia and Resuscitation Department at Zeralda Hospital, and the collected data were statistically analyzed using the Principal Component Analysis method with SPSS V26. The study found that several dimensions are crucial for human capital development, with the most important being investment in knowledge, skills, and expertise, as well as motivating individuals and encouraging communication among them. The study recommended that healthcare institutions adopt the best practices for investing in and developing human capital to address healthcare challenges, as was demonstrated during the COVID-19 crisis. This would positively reflect on the overall performance of the healthcare sector and lead to improved quality of healthcare services.